Analysis of The Effect of Competence and Work Placement on Public Service Performance Through “Satriya” Work Culture in Samsat Bantul - Feriyati Suharto; Kusuma Chandra Kirana; Syamsul Hadi (Universitas Pamulang, 2022)
Employee performance is important in an organization. Public services are also the main target of implementing activities at the Bantul Samsat. As for the competence and staffing conditions of employees, they are the most important part of the service. The main objective of this study is to determine whether competence and work placement have a significant effect on the performance of public services through the work culture of SATRIYA in Samsat Bantul. This research uses descriptive analysis method and inference. Meanwhile, the data collection method used a saturated sample or non-probability sampling by distributing questionnaires to all 50 employees in Samat Bantul. The results showed that competence and work placement had a positive and significant impact on the performance of public services through the work culture of SATRIYA in Samsat Bantul.